H∞Gain-Scheduled Algorithm Design for Multi Coupled Tank - Acosta-Barbosa, K; Zolorza-Vidal, J (Institute of Electrical and Electronics Engineers Inc., 2021)
This work deals with the four connected tanks control and modeling with multiple operation points formulated as a lineal parameter variant (LPV) system. The first step is modeling the plant as a non-linear system and then using its linearization to develop an LPV system based on multiple operation points. Next, knowing the parameters bounds, an H∞ robust and an H∞ gain-scheduling control is designed to the LPV model in order to minimize the perturbation effect in the system output. A numerical example based on a real academic plant is presented to show the proposed approach s effectiveness. © 2021 IEEE.